The Right to Appeal in Indictable Cases: A Legislative History - Buono, Vincent M. Del (Alberta Law Review, 1978)
The author traces the history of criminal appeals legislation in Canada from the Crown Cases Act of 1848 to the present. Through his analysis he illustrates the various forces giving rise to change and amendment, with special emphasis on the strong and often inappropriate influence of British legislation. In addition, the author examines the aim of national uniformity in criminal procedure, and the way in which appeals legislation has fostered this aim.